Angst in the household - Hartin, Patrick (Neotestamentica, 1988)
Interpolation has to take into consideration three poles: author, text and interpreter. In the field of literary studies deconstruction has provoked much interest and concern. The scope of this paper is to illustrate this activity of deconstruction unfolding by means of a reading of the parable of the Supervising Servant. This illustration from the Scriptures shows what happens to every text which is read again. It is reinterpreted anew according to new contexts. It is an example of the dissemination of the Word, whereby the Word becomes flesh.